PENURUNAN KADAR BESI (II) PADA AIR BERSIH MENGGUNAKAN AMPAS DAUN TEH DIAKTIVASI - Laili Purwaningsih; Rachmaniyah .; Pratiwi Hermiyanti (Poltekkes Kemenkes Surabaya, 2019)
The production of dried tea leaves and tea consumption in Indonesia has increased from year to year. This condition was directly proportional to the spent tea leaves produced. Spent tea leaves contained 37% cellulose which can adsorb heavy metals in polluted water. Iron (II) metal was often found in high concentrations in ground water, so a treatment process was needed. This study aimed to analyze the removal of iron (II) in water by using activated spent tea leaves.The type of this research was true experiment with a pretest-posttest controlled group design. Spent tea leaves with size 80 mesh was activated with 0.1 N HCl for 36 hours. The method was carried out with a batch system in an artificial iron solution the initial concentration was 9.85 mg / L, with mass of adsorbent was 10 grams, pH = 7, stirring speed 100 rpm, contact time 15 minutes, 25 minutes, and 35 minutes. Measurement of iron levels was carried out before and after treatment using the SSA method. FTIR test carried out before and after activated spent tea leaves were used adsorption. Data analysis was carried out descriptively and analytically (One-way Anova Test and LSD Test).The results showed that activated spent tea leaves can remove iron (II) levels in water. The result of One-way Anova test and LSD test, the higgest removal of iron (II) occurred at 35 minutes contact time with adsorption efficiency was 90.36%. FTIR test results showed that activated spent tea leaves in this study contained functional groups were O-H, C-H, C=O, C=C, and C-N.This study concluded that activated spent tea leaves can remove iron (II) in water. The higgest removal of iron (II) occurred at 35 minutes contact time. Further research is needed to achieve 100% adsorption efficiency and find an effort to reduce turbidity in sample water after treatment. Keywords: Clean Water, Iron (II), Spent tea leaves